Standardization and preliminary phytochemical screening of Kodiveli chooranum - Varuna, V.; Thayalini, T.; Velauthamurty, K.; Manoranjan, T. (Faculty of Science, University of Kelaniya, Sri Lanka, 2024)
Traditional medicinal systems (Ayurveda, Siddha, and Unani) impact people's health care and deal with herbo mineral preparation. More than 80% of the population uses herbs and herbal products for primary health care. Standardization is crucial in drug manufacturing and the safety, efficacy, and, quality of the medicines necessity to be analyzed before commercialization. The polyherbal concoction of Kodivelich chooranum (KC) is a chooranum under the 32 types of internal medicine mentioned in Siddha literature which is used for treating skin disorders (kiranthi, kuttam, and puzhuveddu). The study aimed to screen the key phytochemicals and establish standardized parameters for the Kodivelich chooranum to ensure safety and efficacy. The plant materials were collected, purified, and prepared the KC chooranum according to the Siddha textbook of Vaithiya pooranam 205. The KC and its constituents were evaluated for important phytochemicals such as glycoside, flavonoid, saponin, tannin, and terpenoid. The standardization of KC was carried out of Ash value, loss on drying at 110 °C, pH value, total solids of aqueous extract, and extractive values. The methanolic and aqueous extract of the KC and individual ingredients showed the presence of glycoside, tannin, flavonoids, saponin, and terpenoids. The value of physicochemical parameters of KC contains total ash 6.29 ± 0.09, acid-insoluble ash 1.66 ± 0.22, pH 6.04 ± 0.08, loss on drying at 110 6.66 ± 0.84, Total solid of aqueous extract 8.93 ± 0.22, Alcohol soluble 4.83 ±0.11, and water-soluble 9.37 ± 1.36. The results of the current investigation showed that all of the examined parameters had values that fell within the WHO's standards. The presence of phytochemicals confirmed this concoction can be used for skin diseases. Future research on antimicrobials will be conducted to evaluate the medication's effectiveness.
Keywords: Kodiveli chooranum; Siddha system of medicine; Physicochemical; Phytochemical